Laminated solar cell and photovoltaic module
By using high light transmittance polymer material as the tunneling layer in laminated solar cells and combining conductive agents, the problem of parasitic absorption of the intermediate tunneling layer is solved, and the light utilization rate and battery performance are improved.
Patent Information
- Application Number
- CN202411616537.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-04-15
AI Technical Summary
In existing stacked solar cells, parasitic absorption of the intermediate tunneling layer leads to low light utilization, resulting in device light absorption loss.
A polymer material is used as the tunneling layer, especially for polymer materials with a light transmittance of more than 800 nm or above, and a conductive agent is combined to improve carrier mobility and conductivity.
It effectively reduces the parasitic absorption of the tunneling layer, improves the light utilization rate and battery performance, enhances the absorption of light of the bottom battery above 800nm, and optimizes the response characteristics of the stacked battery in a wide spectral range.
Smart Images

Figure CN119836128A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of solar cells, and in particular to a stacked solar cell and a photovoltaic module. Background Art
[0002] Solar energy is a renewable energy source, and a single solar cell has limited utilization of the full wavelength of solar energy. However, stacked cells can absorb short-wave and long-wave light through the top cell and bottom cell respectively, achieving efficient utilization of solar energy. However, a fully covered transparent conductive oxide film is often used as an intermediate tunneling layer between the top cell and the bottom cell. The existing intermediate tunneling layer usually has a transmittance of less than 90% for light with a wavelength of 300~1200nm, resulting in light absorption loss of the device. Summary of the invention
[0003] The purpose of the present disclosure is to provide a stacked solar cell and a photovoltaic module, which can effectively reduce the parasitic absorption of the intermediate tunneling layer and improve the light utilization rate and cell performance.
[0004] In order to achieve the above-mentioned object, the present disclosure provides a stacked solar cell in a first aspect, comprising a stacked bottom cell, a tunneling layer and a perovskite top cell; the tunneling layer comprises a polymer material, and the transmittance of the polymer material to light with a wavelength of more than 800 nm reaches more than 92%; the carrier mobility of the tunneling layer is 10 2 cm 2 / VS and above.
[0005] Optionally, the polymer material is selected from one or more of silicone polymers, aliphatic polymers and aromatic polymers.
[0006] Optionally, the silicone polymer includes polydimethylsiloxane; The aliphatic polymer includes one or more of ethylene-vinyl acetate copolymer, ethylene propylene diene monomer rubber and polyacetylene; The aromatic polymer includes one or more of polythiophene, polyaniline, polypyrrole and polyethylenedioxythiophene.
[0007] Optionally, the polymer material comprises at least one of polydimethylsiloxane, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber. Optionally, based on the total weight of the tunneling layer, the content of the polymer material is 60-80 wt%.
[0008] Optionally, the molecular weight of the polydimethylsiloxane is 500~100000; the molecular weight of the ethylene-vinyl acetate copolymer is 2000~500000; the molecular weight of the ethylene propylene diene rubber is 50000~150000; the molecular weight of the polyacetylene is 1000~100000; the molecular weight of the polythiophene is 1000~100000; the molecular weight of the polyaniline is 1000~100000; the molecular weight of the polyaniline is 1000~100000; the molecular weight of the polypyrrole is 1000~100000; the molecular weight of the polyethylene dioxythiophene is 1000~100000.
[0009] Optionally, the ethylene-vinyl acetate copolymer comprises ethylene structural units and vinyl acetate structural units; based on the total weight of the ethylene-vinyl acetate copolymer, the content of the ethylene structural units is 40-80% by weight, and the content of the vinyl acetate structural units is 20-60% by weight; The EPDM rubber comprises ethylene structural units, propylene structural units and non-conjugated diene structural units; based on the total weight of the EPDM rubber, the content of the ethylene structural units is 42-70% by weight, the content of the propylene structural units is 29-55% by weight, and the content of the non-conjugated diene structural units is 1-3% by weight.
[0010] Optionally, the tunneling layer further comprises a conductive agent; the conductive agent comprises one or more of graphene, conductive carbon black and carbon nanotubes; And / or, the particle size of the conductive agent is 5 to 5000 nm; And / or, based on the total weight of the tunneling layer, the content of the conductive agent is 20-50 wt %.
[0011] Optionally, the carrier mobility of the tunneling layer is 10 2 ~10 4 cm 2 / VS.
[0012] Optionally, the tunneling layer has a thickness of 1-300 nm.
[0013] Optionally, the thickness of the tunneling layer is 5-50 nm.
[0014] Optionally, the perovskite top cell comprises a stacked hole transport layer, a perovskite absorption layer, an electron transport layer and a conductive electrode; the hole transport layer is laminated to the tunneling layer; The bottom cell is a crystalline silicon bottom cell.
[0015] Optionally, the thickness of the hole transport layer is 20-500 nm; the total thickness of the hole transport layer and the tunneling layer is 50-800 nm; The thickness of the perovskite absorption layer is 300-800 nm; the band gap of the perovskite absorption layer is 1.6-1.8 eV; The thickness of the electron transport layer is 20-100 nm.
[0016] Optionally, the perovskite absorption layer comprises one or more compounds having the general formula shown in the following formula (1): ABX3 formula (1); where A is selected from Cs + 、C2H8N + 、CH5N2 + and CH6N + One or more of the following; B is Pb 2+ ; X is selected from Cl - Br - and I - One or more of; and / or The crystalline silicon bottom cell is selected from one of PERC, TOPCon and HJT.
[0017] A second aspect of the present disclosure provides a photovoltaic module, comprising the stacked solar cell described in the first aspect of the present disclosure.
[0018] Through the above technical scheme, the present disclosure provides a stacked solar cell and a photovoltaic module. The stacked solar cell uses a new polymer material of the tunneling layer, which has better light transmittance than the commonly used transparent conductive oxide, especially higher transmittance for wavelengths above 800nm, can avoid light loss caused by the tunneling layer, reduce the parasitic absorption of light by the tunneling layer, and improve the overall light utilization efficiency; the tunneling layer has a high carrier mobility and good conductivity. The top cell and the bottom cell of the solar cell absorb short-wave and long-wave light respectively, and by reducing the light absorption loss of the middle layer (tunneling layer), the bottom cell absorbs light above 800nm, further improving the overall photoelectric conversion efficiency of the perovskite stacked cell. The tunneling layer provided by the present disclosure can better match the light absorption region (800~1400nm) of the bottom cell, optimize the response characteristics of the stacked cell in a wide spectral range, and make it perform better under various lighting conditions. The tunneling layer provided by the present disclosure can be optimized and improved on the basis of the existing production process, has good process compatibility, and is conducive to large-scale production and application promotion.
[0019] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings: Figure 1 A schematic diagram of the structure of a stacked solar cell provided by the present disclosure; Figure 2 This is the ultraviolet absorption spectrum of the tunneling layer in Comparative Example 1.
[0021] Reference numerals 11-bottom cell, 110-first electrode, 111-first transparent conductive layer, 112-p-type amorphous / microcrystalline silicon layer, 113-second passivation layer, 114-n-type crystalline silicon wafer, 115-first passivation layer, 116-n-type amorphous / microcrystalline silicon layer; 21-perovskite top cell, 211-hole transport layer, 212-perovskite absorption layer, 213-electron transport layer, 214-work function adjustment layer, 210-second electrode, 31-tunneling layer. DETAILED DESCRIPTION
[0022] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0023] The first aspect of the present disclosure provides a stacked solar cell, such as Figure 1 As shown, it includes a stacked bottom cell 11, a tunneling layer 31 and a perovskite top cell 21; the tunneling layer 31 includes a polymer material, and the transmittance of the polymer material to light with a wavelength of more than 800 nm reaches more than 92%; the carrier mobility of the tunneling layer is 10 2 cm 2 / VS and above.
[0024] The present disclosure provides a stacked solar cell, which uses a new polymer material for the tunneling layer, which has better light transmittance than the commonly used transparent conductive oxide, especially higher transmittance for wavelengths above 800nm, can avoid light loss caused by the tunneling layer, reduce the parasitic absorption of light by the tunneling layer, and improve the overall light utilization efficiency. The top cell and the bottom cell of the solar cell absorb short-wave and long-wave light respectively, and enhance the absorption of light with a wavelength of more than 800nm by the bottom cell by reducing the light absorption loss of the middle layer (tunneling layer); the carrier mobility of the tunneling layer is high, and it has good conductivity, which further improves the overall photoelectric conversion efficiency of the perovskite stacked cell. The tunneling layer provided by the present disclosure can better match the light absorption region (800~1400nm) of the bottom cell, optimize the response characteristics of the stacked cell in a wide spectral range, and make it perform better under various lighting conditions. The tunneling layer provided by the present disclosure can be optimized and improved on the basis of the existing production process, has good process compatibility, and is conducive to large-scale production and application promotion.
[0025] In one embodiment, the polymer material is selected from one or more of an organosilicon polymer, an aliphatic polymer and an aromatic polymer. In the present disclosure, an organosilicon polymer refers to a polymer main chain containing Si atoms; an aliphatic polymer refers to a polymer main chain composed of an aliphatic compound, such as containing three elements of C, H, and O; an aromatic polymer refers to a polymer main chain containing an aromatic ring, which includes not only a benzene ring, but also an aromatic ring structure with heteroatoms, such as a thiophene ring, a pyrrole ring, and the like.
[0026] In one specific embodiment, the organosilicon polymer includes polydimethylsiloxane; The aliphatic polymer includes one or more of ethylene-vinyl acetate copolymer, ethylene propylene diene monomer rubber and polyacetylene; The aromatic polymer includes one or more of polythiophene, polyaniline, polypyrrole and polyethylenedioxythiophene. The specific polymer materials provided in this embodiment can all play an excellent role in the tunneling layer of the stacked solar cell and improve the light transmittance of the tunneling layer.
[0027] In a preferred embodiment, the polymer material includes at least one of polydimethylsiloxane, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber. The polymer material provided in this embodiment has a higher light transmittance for light above 800 nm, which can reach more than 95%, or even more than 98%.
[0028] In a preferred embodiment, based on the total weight of the tunneling layer, the content of the polymer material is 60-80% by weight, preferably 65-75% by weight. When the content of the polymer material in the tunneling layer is within the range of this embodiment, especially within the preferred range, it can be ensured that the tunneling layer has a higher light transmittance.
[0029] In one embodiment, the molecular weight of the polydimethylsiloxane is 500-100000, preferably 5000-10000; the molecular weight of the ethylene-vinyl acetate copolymer is 2000-500000, preferably 5000-10000; the molecular weight of the EPDM rubber is 5000-150000, preferably 30000-80000; the molecular weight of the polythiophene is 1000-100000, preferably 1000 0~50000; the molecular weight of the polyaniline is 1000~100000, preferably 30000~60000; the molecular weight of the polypyrrole is 1000~100000, preferably 20000~50000; the molecular weight of the polyacetylene is 1000~100000, preferably 20000~80000; the molecular weight of the polyethylenedioxythiophene is 1000~100000, preferably 30000~50000. When the molecular weight of the polymer material is within the range of this embodiment, it is beneficial to reduce the parasitic absorption of the tunneling layer and improve the light utilization efficiency.
[0030] In one embodiment, the ethylene-vinyl acetate copolymer comprises ethylene structural units and vinyl acetate structural units; based on the total weight of the ethylene-vinyl acetate copolymer, the content of the ethylene structural units is 40-80% by weight, preferably 45-65% by weight; the content of the vinyl acetate structural units is 20-60% by weight, preferably 35-55% by weight; The EPDM rubber includes ethylene structural units, propylene structural units and non-conjugated diene structural units; based on the total weight of the EPDM rubber, the content of the ethylene structural units is 42-70% by weight, preferably 45-60% by weight, the content of the propylene structural units is 29-55% by weight, preferably 37-52% by weight, and the content of the non-conjugated diene structural units is 1-3% by weight, preferably 2-3% by weight. When the content of each structural unit of the polymer material is within the range of this embodiment, especially within the preferred range, the light transmittance can be further improved, thereby improving the performance of the battery.
[0031] The polymer materials used in the present disclosure can be purchased through common commercial channels, or can be prepared by known methods.
[0032] In one embodiment, the tunneling layer further comprises a conductive agent; the conductive agent is selected from one or more of graphene, conductive carbon black and carbon nanotubes. The tunneling layer provided by the present disclosure has high transmittance while maintaining high conductivity, which helps to reduce the resistance loss of the device and improve the fill factor and output power of the battery.
[0033] In a preferred embodiment, based on the total weight of the tunneling layer, the content of the conductive agent is 20-50% by weight, preferably 25-45% by weight. Adding the conductive agent according to the content in this embodiment, especially according to the preferred content, is conducive to ensuring high light transmittance of the tunneling layer while taking into account high conductivity.
[0034] In a specific embodiment, the particle size of the conductive agent is 5 to 5000 nm, preferably 50 to 500 nm.
[0035] In one embodiment, the carrier mobility of the tunneling layer is 10 2 ~10 4 cm 2 / VS, the tunneling layer provided by the present disclosure has excellent conductivity.
[0036] In one embodiment, the thickness of the tunneling layer is 1-300 nm, preferably 5-50 nm. When the thickness of the tunneling layer is within the range of this embodiment, especially within the preferred range, it has a better electron transport effect.
[0037] The tunneling layer in the present disclosure can be prepared by conventional processes, such as by ink printing process.
[0038] In a specific implementation manner, Figure 1 As shown, the perovskite top cell includes a stacked hole transport layer 211, a perovskite absorption layer 212, an electron transport layer 213, a work function adjustment layer 214, and a second electrode 210; the hole transport layer 211 is laminated with the tunneling layer 31; The bottom cell is a crystalline silicon cell. The crystalline silicon bottom cell and the perovskite top cell disclosed in the present invention can be conventional structures in the field. And the above functional layers are conformal (i.e., have the same morphology) with the crystalline silicon cell. For example, if the silicon surface of the bottom cell is velvet, then the functional layers such as the perovskite absorption layer of the top cell are grown on the velvet structure; if the silicon of the bottom cell is flat and polished, then the functional layers such as the perovskite absorption layer of the top cell are grown on a flat surface.
[0039] In a specific embodiment, the tandem solar cell comprises the following steps: S1, preparing a bottom battery 11; S2, depositing an intermediate composite layer (tunneling layer 31) on the bottom battery 11; depositing a hole transport layer 211 on the tunneling layer 31; the tunneling layer 31 and the hole transport layer 211 are both conformal with the bottom battery; S3, preparing a perovskite absorption layer 212 on the hole transport layer 211; the perovskite absorption layer 212 is conformal to the bottom cell 11; S4, depositing an electron transport layer 213 and a work function adjustment layer 214 in sequence on the perovskite absorption layer 212 ; and disposing a second electrode 210 on the work function adjustment layer 214 .
[0040] In a preferred embodiment, the thickness of the hole transport layer is 20~500nm, preferably 50~100nm; the total thickness of the hole transport layer and the tunneling layer is 50~800nm, preferably 80~200nm; controlling the total thickness of the hole transport layer and the tunneling layer within the range of this embodiment is conducive to promoting electron transport.
[0041] In one embodiment, the thickness of the perovskite absorption layer is 300-800 nm, preferably 400-600 nm, which has a better photoelectric conversion effect.
[0042] In one embodiment, the band gap of the perovskite absorption layer is 1.5-1.8 eV, preferably 1.55-1.65 eV, and the utilization rate of sunlight below 800 nm is higher.
[0043] In a specific embodiment, the perovskite absorption material of the perovskite absorption layer includes one or more compounds having the general formula shown in the following formula (1): ABX3 formula (1); where A is selected from Cs + 、C2H8N + 、CH5N2 + and CH6N + One or more of the following; B is Pb 2+ ; X is selected from Cl - Br - and I - One or more of the above. The perovskite absorption material having the structure of formula (1) has excellent photoelectric conversion effect.
[0044] In one embodiment, the perovskite absorption layer can be formed by multi-source co-evaporation deposition of perovskite precursor materials, and the number of evaporation sources of the multi-source co-evaporation can be 2 to 4; it can also be prepared by a coating process. In the present disclosure, the co-evaporation process or coating process of the perovskite absorption layer can be carried out using conventional processes in the art.
[0045] In a preferred embodiment, after the perovskite absorption layer is prepared on the hole transport layer, annealing is performed; the annealing temperature can be 70~120°C, and the annealing time can be 5~40min; preferably, the annealing temperature can be 100~150°C, and the annealing time can be 10~30min. Through annealing treatment, the growth of perovskite grains can be promoted, the perovskite crystals can be stabilized, and the overall performance of the stacked solar cell can be improved.
[0046] In a specific embodiment, the perovskite precursor material includes a first raw material and a second raw material; the first raw material includes one or more of PbI2, PbBr2 and PbCl2; the second raw material includes one or more of CsI, CsBr, CsCl, DMAI (dimethylamine hydroiodide, C2H8IN), FAI (formamidine hydroiodide, CH5IN2) and MACl (methylammonium chloride, CH3NH3Cl). By combining the above compounds, a perovskite absorption layer with better performance can be formed.
[0047] In a preferred embodiment, the raw materials for preparing the hole transport layer include poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 3-hexylthiophene polymer (P3HT), cuprous iodide (CuI), cuprous thiocyanate (CuSCN), nickel oxide (NiOx), copper porphyrin complex (CuPc), and self-assembled monolayer (SAM) materials with acetate, boric acid, thiol, phosphonic acid, etc. The hole transport layer is prepared using the above raw materials, which can have the effect of transporting holes. According to the properties of the raw materials of the hole transport layer, it can be prepared by magnetron sputtering or reactive plasma deposition, or it can also be prepared by thermal evaporation. For example, when the hole transport layer is nickel oxide, the hole transport layer is prepared by magnetron sputtering or reactive plasma deposition; when the hole transport layer is Spiro-TTB, MeO-2PACz or P3HT, the hole transport layer is prepared by thermal evaporation. The specific preparation process conditions are conventional conditions in the art.
[0048] In a preferred embodiment, the method further comprises depositing a passivation layer between the perovskite absorption layer and the electron transport layer. The raw material of the passivation layer comprises PEAI and / or PDADI, which is conducive to passivating the defects of the perovskite surface layer.
[0049] In one embodiment, the raw materials for preparing the electron transport layer include SnO2, TiO2, ZnO2, tungsten oxide, PC 61 BM, PC 71 BM, C 60 and C 70 One or more of the above can improve the transmission efficiency of electrons.
[0050] In a specific embodiment, the method further comprises depositing a work function adjustment layer on the electron transport layer, including but not limited to one of BCP. By providing the work function adjustment layer, hole transport can be blocked.
[0051] In one implementation, the conductive electrode may be made of Ag.
[0052] In one embodiment, the type of the crystalline silicon bottom cell may be one of PERC, TOPCon, and HJT, and may be prepared by conventional methods.
[0053] In a specific implementation, taking an n-type silicon substrate cell as an example, Figure 1 As shown, the crystalline silicon bottom cell includes a first electrode 110, a first transparent conductive layer 111, a p-type amorphous / microcrystalline silicon layer 112, a second passivation layer 113, an n-type crystalline silicon wafer 114, a first passivation layer 115, and an n-type amorphous / microcrystalline silicon layer 116, and its manufacturing method includes the following steps: In the first step, an n-type crystalline silicon wafer 114 is prepared. In practical applications, the n-type crystalline silicon wafer 114 is a commercial-grade silicon wafer with a resistivity of 1 Ω.cm-10 Ω.cm and a thickness of 50 μm-300 μm.
[0054] In the second step, the n-type crystalline silicon wafer 114 is subjected to texturing and cleaning treatments in sequence to form a textured n-type crystalline silicon wafer 114. The n-type crystalline silicon wafer 114, as a light absorption layer of a silicon-based solar cell, converts photons into photogenerated carriers (electron-hole pairs).
[0055] In the third step, an intrinsic amorphous silicon passivation layer is deposited on both sides of the n-type crystalline silicon wafer 114 to form a first passivation layer 115 located on the front side of the n-type crystalline silicon wafer 114 and a second passivation layer 113 located on the back side of the n-type crystalline silicon wafer 114. The first passivation layer 115 and the second passivation layer 113 mainly play the role of passivating the dangling bonds on the surface of the n-type crystalline silicon wafer 114.
[0056] In practical applications, the intrinsic amorphous silicon passivation layer can be manufactured by plasma chemical vapor deposition (PECVD), hot wire chemical vapor deposition, catalytic chemical vapor deposition, etc. The thickness of the first passivation layer 115 and the second passivation layer 113 can be 1nm-20nm.
[0057] In the fourth step, a phosphorus-doped n-type amorphous / microcrystalline silicon layer 116 is deposited on the first passivation layer 115 to form a front emitter. In practical applications, the n-type amorphous / microcrystalline silicon layer 116 can be made by PECVD, hot wire chemical vapor deposition, catalytic chemical vapor deposition and other processes. The thickness of the n-type amorphous / microcrystalline silicon layer 116 can be 1nm-30nm.
[0058] In the fifth step, a boron-doped p-type amorphous / microcrystalline silicon layer 112 is deposited on the second passivation layer 113 to form a back field structure. In practical applications, the p-type amorphous / microcrystalline silicon layer 112 can be made by PECVD, hot wire chemical vapor deposition, catalytic chemical vapor deposition and other processes. The thickness of the p-type amorphous / microcrystalline silicon layer 112 can be 1nm-30nm.
[0059] In the sixth step, a first transparent conductive layer 111 is formed on the p-type amorphous / microcrystalline silicon layer 112. The first transparent conductive layer 111 mainly collects photogenerated carriers and transmits the photogenerated carriers to the back metal electrode (first electrode) 110. Specifically, the material of the first transparent conductive layer 111 can be one or more of indium tin oxide (ITO), tungsten-doped indium oxide (IWO), indium zinc oxide (IZO), and titanium-doped indium oxide (ITiO), but is not limited thereto.
[0060] In practical applications, the first transparent conductive layer 111 may be manufactured by a magnetron sputtering process. The thickness of the first transparent conductive layer 111 may be 30 nm to 120 nm.
[0061] The above process steps produce a silicon-based cell. Since the crystalline silicon substrate has a suede structure, the first transparent conductive layer 111, the p-type amorphous / microcrystalline silicon layer 112, the second passivation layer 113, the first passivation layer 115, and the n-type amorphous / microcrystalline silicon layer 116 formed on the crystalline silicon substrate also have a suede structure.
[0062] A second aspect of the present disclosure provides a photovoltaic module, comprising the stacked solar cell described in the first aspect of the present disclosure.
[0063] The present disclosure is further described in detail below in conjunction with embodiments.
[0064] The molecular weight of polymer materials was obtained by gel permeation chromatography (GPC) testing; The contents of different structural units in polymer materials were obtained by gel permeation chromatography (GPC) testing; The UV absorption spectrum of the sample was obtained by UV-visible spectrophotometer. The carrier mobility of the tunneling layer is measured by the Hall effect method.
[0065] Example 1 This example is used to prepare Figure 1 The stacked solar cell shown comprises the following steps: (1) Obtaining a HJT silicon substrate cell (bottom cell 11); (2) Preparing an intermediate composite layer (tunneling layer 31) on the surface of the silicon substrate battery, comprising the following steps: 3 mg of graphene (conductive agent) was dissolved in 3 mL of PDMS (polydimethylsiloxane, a polymer material with a transmittance of more than 95% at wavelengths above 800 nm and a molecular weight of 5000) solution, the solvent was n-hexane, the concentration of PDMS was 80% by weight, and the doping amount of the conductive agent (graphene) was 1 mg / mL. A high-speed homogenizer was used to stir at 30,000 rpm for 2 hours at room temperature to obtain a PDMS polymer ink doped with graphene, and then the ink was spin-printed on the surface of the bottom battery by a printing method to form a thin film to obtain a tunneling layer.
[0066] Based on the total weight of the tunneling layer, the content of the polymer material is 60% by weight, and the content of the conductive agent (graphene) is 40% by weight; the thickness of the obtained tunneling layer is 30 nm, and the carrier mobility of the tunneling layer is 5×10 3 cm 2 / VS.
[0067] (3) Prepare 50 nm thick NiO on the tunneling layer 31 x (hole transport layer 211, the total thickness of the hole transport layer and the tunneling layer is 80 nm), 500 nm thick FAPbI3 (CH(NH2)2PbI3, that is, A in formula (1) is CH5N2 + ) as the main component of the perovskite film (perovskite absorption layer 212, the band gap of the perovskite absorption layer is 1.48eV), 10 nm of PEAI (phenylethylammonium iodide, passivation layer, not shown in the figure), 80 nm thick C 60 (electron transport layer 213) and 10 nm thick BCP (work function adjustment layer 214), and set a metal electrode Ag (second electrode 210) to obtain a perovskite top cell 21. The first raw material used in the perovskite absorption layer is FAI, the second raw material is PbI2, and the molar ratio of the first raw material to the second raw material is 1:1.
[0068] Comparative Example 1 This comparative example refers to the preparation process of the laminated solar cell in Example 1, and the difference from Example 1 is that: The material of the tunneling layer is replaced with FTO (fluorine-doped tin oxide), and no conductive agent is added. The rest of the process is the same as in Example 1.
[0069] The structure of the battery obtained in this comparative example is as follows Figure 1 As shown, the material of the tunneling layer is FTO; the ultraviolet absorption spectrum of the tunneling layer of the battery is as shown Figure 2 As shown, it can be seen that the use of existing FTO materials makes the transmittance of the tunneling layer for the band above 800nm less than 92.8%. The transmittance of the tunneling layer made of the polymer material provided by the present disclosure in Example 1 is higher.
[0070] Example 2 This embodiment refers to the battery preparation method in Example 1, and the difference from Example 1 is that: The polymer material PDMS solution in the tunneling layer is replaced with an ethylene-vinyl acetate copolymer (EVA, molecular weight of 10,000, ethylene structural unit content of 50% by weight, vinyl acetate structural unit content of 50% by weight) solution, the solvent is benzene, the concentration of EVA is 50% by weight, and the doping amount of the conductive agent is 1 mg / mL to obtain a tunneling layer. Based on the total weight of the tunneling layer, the content of the polymer material is 60% by weight, and the content of the conductive agent is 40% by weight.
[0071] Example 3 This embodiment refers to the battery preparation method in Example 1, and the difference from Example 1 is that: The polymer material PDMS solution in the tunneling layer is replaced with an ethylene propylene diene monomer (EPDM, molecular weight 50,000, ethylene structural unit content 56% by weight, propylene structural unit content 42% by weight, non-conjugated diene structural unit content 2% by weight) solution, the solvent is cyclohexane, the concentration of EPDM is 70% by weight, and the doping amount of the conductive agent is 1 mg / mL to obtain a tunneling layer. Based on the total weight of the tunneling layer, the content of the polymer material is 60% by weight, and the content of the conductive agent is 40% by weight.
[0072] Example 4 This embodiment refers to the battery preparation method in Example 1, and the difference from Example 1 is that: The polymer material PDMS solution in the tunneling layer is replaced with a polythiophene (molecular weight 20,000) solution, the solvent is tetrahydrofuran, the concentration of polythiophene is 45% by weight, and the doping amount of the conductive agent is 1 mg / mL, to obtain a tunneling layer. Based on the total weight of the tunneling layer, the content of the polymer material is 60% by weight, and the content of the conductive agent is 40% by weight.
[0073] Example 5 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The coating amount of the graphene-doped PDMS polymer ink was adjusted so that the thickness of the resulting tunneling layer was 200 nm.
[0074] Example 6 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The thickness of the hole transport layer is adjusted to 400 nm, so that the total thickness of the hole transport layer and the tunneling layer is 430 nm.
[0075] Example 7 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The thickness of the perovskite absorber layer was set to 800 nm.
[0076] Example 8 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The amount of the polymer material added was adjusted. Based on the total weight of the tunneling layer, the content of the polymer material was 70% by weight, and the content of the conductive agent was 30% by weight.
[0077] Example 9 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The amount of the polymer material added was adjusted. Based on the total weight of the tunnel layer, the content of the polymer material was 40% by weight, and the content of the conductive agent was 60% by weight.
[0078] Example 10 This example refers to the preparation method in Example 1, and the difference from Example 1 is that: The amount of the polymer material added was adjusted. Based on the total weight of the tunneling layer, the content of the polymer material was 95% by weight, and the content of the conductive agent was 5% by weight.
[0079] Embodiment 11 This example refers to the preparation method in Example 2, and the difference from Example 2 is that: In the adopted ethylene-vinyl acetate copolymer, based on the total weight of the ethylene-vinyl acetate copolymer, the content of the ethylene structural unit is 20% by weight; and the content of the vinyl acetate structural unit is 80% by weight.
[0080] Example 12 This example refers to the preparation method in Example 3, and the difference from Example 3 is that: In the EPDM rubber used, based on the total weight of the EPDM rubber, the content of the ethylene structural unit is 80% by weight, the content of the propylene structural unit is 10% by weight, and the content of the non-conjugated diene structural unit is 10% by weight.
[0081] Test Case The transmittance of the tunneling layer in the battery obtained in the above embodiment and comparative example to wavelengths above 800 nm was tested, and the testing instrument and testing method included: using an ultraviolet-visible spectrophotometer to test the absorption coefficient in the range of 300-1400 nm.
[0082] The performance of the cells obtained in the above embodiments and comparative examples was tested, and the testing instrument and testing method included: using a photovoltaic module IV tester to test the efficiency, open circuit voltage, short circuit current and fill factor of the stacked cell device.
[0083] The test results are listed in Table 1 below.
[0084] Table 1
[0085] According to the data in Table 1: Compared with the stacked solar cell in comparative example 1 (the material of the tunneling layer is FTO), the tunneling layer in the stacked solar cells in Examples 1 to 12 has a higher average transmittance for light with a wavelength of 800 to 1400 nm, and a higher carrier mobility of the tunneling layer, indicating that the tunneling layer of the stacked solar cell provided by the present disclosure can have a higher light utilization rate and a higher conductivity; the cell efficiency, open circuit voltage and short circuit current of the stacked solar cells in Examples 1 to 12 are also higher, and the cell performance is better; Comparing Example 1 with Examples 9-10, it can be seen that in the tunneling layer of Example 1, the content of the polymer material is within the optimized range provided by the present disclosure (60-80 weight %), while the content of the polymer material in Examples 9-10 is not within the optimized range. In the laminated solar cell obtained in Example 1, the tunneling layer has a higher average transmittance for light with a wavelength of 800-1400 nm, and the battery efficiency and short-circuit current of the battery are also higher, and the battery performance is better. Further comparison of Example 1 with Example 8 shows that in the tunneling layer of Example 8, the content of the polymer material is within the further preferred range provided in the present disclosure (65-75 wt %), the tunneling layer of Example 8 has higher carrier mobility, and the cell efficiency, open circuit voltage and short circuit current of the stacked solar cell are also higher, and the cell performance is better; Comparing Example 11 with Example 2, the contents of ethylene structural units and vinyl acetate structural units in the polymer material ethylene-vinyl acetate copolymer used in the tunneling layer in Example 2 are within the optimization range provided by the present disclosure. Compared with the stacked cell in Example 11, the tunneling layer in the stacked solar cell in Example 2 has a higher average transmittance for light with a wavelength of 800-1400nm, and a higher carrier mobility of the tunneling layer; the cell efficiency, open circuit voltage and short circuit current of the stacked solar cell are also higher, and the cell performance is better; Comparing Example 12 with Example 3, the content of each structural unit in the polymer material EPDM rubber used in the tunneling layer in Example 3 is within the optimization range provided by the present disclosure. Compared with the stacked cell in Example 12, the stacked solar cell in Example 3 has a higher carrier mobility in the tunneling layer; the stacked solar cell also has higher cell efficiency, open circuit voltage and short circuit current, and better cell performance; Comparing Example 1 with Example 5, the thickness of the tunneling layer in Example 1 is within the preferred range provided in the present disclosure, the average transmittance and carrier mobility of the tunneling layer of the battery obtained in Example 1 for light with a wavelength of 800-1400 nm are higher, the battery efficiency, open circuit voltage and short circuit current of the stacked battery are also higher, and the battery performance is better; Comparing Example 1 with Example 6, the thickness of the hole transport layer and the total thickness of the hole transport layer and the tunnel layer in Example 1 are within the preferred range provided by the present disclosure, and the battery efficiency and short-circuit current of the laminated battery obtained in Example 1 are higher, and the battery performance is better; Comparing Example 1 with Example 7, the thickness of the perovskite absorption layer in Example 1 is within the preferred range provided in the present disclosure, the battery efficiency and open circuit voltage of the stacked battery obtained in Example 1 are significantly higher than those in Example 7, and the battery obtained in Example 1 has better performance.
[0086] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0087] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0088] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A stacked solar cell, characterized in that: The invention comprises a bottom cell, a tunneling layer and a perovskite top cell which are stacked; the tunneling layer comprises a polymer material, and the transmittance of the polymer material to light with a wavelength of more than 800 nm reaches more than 92%; the carrier mobility of the tunneling layer is 10 2 cm 2 / VS and above.
2. The solar cell according to claim 1, characterized in that: The polymer material is selected from one or more of silicone polymers, aliphatic polymers and aromatic polymers.
3. The solar cell according to claim 2, characterized in that: The silicone polymer includes polydimethylsiloxane; The aliphatic polymer includes one or more of ethylene-vinyl acetate copolymer, ethylene propylene diene monomer rubber and polyacetylene; The aromatic polymer includes one or more of polythiophene, polyaniline, polypyrrole and polyethylenedioxythiophene.
4. The solar cell according to claim 1, characterized in that The polymer material includes at least one of polydimethylsiloxane, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber.
5. The solar cell according to claim 1, characterized in that: Based on the total weight of the tunneling layer, the content of the polymer material is 60-80% by weight.
6. The tandem solar cell according to claim 3, characterized in that: The molecular weight of the polydimethylsiloxane is 500-100000; the molecular weight of the ethylene-vinyl acetate copolymer is 2000-500000; the molecular weight of the ethylene propylene diene rubber is 50000-150000; the molecular weight of the polyacetylene is 1000-100000; the molecular weight of the polythiophene is 1000-100000; the molecular weight of the polyaniline is 1000-100000; the molecular weight of the polyaniline is 1000-100000; the molecular weight of the polypyrrole is 1000-100000; and the molecular weight of the polyethylene dioxythiophene is 1000-100000.
7. The tandem solar cell according to claim 4, characterized in that: The ethylene-vinyl acetate copolymer comprises an ethylene structural unit and a vinyl acetate structural unit; based on the total weight of the ethylene-vinyl acetate copolymer, the content of the ethylene structural unit is 40-80% by weight, and the content of the vinyl acetate structural unit is 20-60% by weight; The EPDM rubber comprises ethylene structural units, propylene structural units and non-conjugated diene structural units; based on the total weight of the EPDM rubber, the content of the ethylene structural units is 42-70% by weight, the content of the propylene structural units is 29-55% by weight, and the content of the non-conjugated diene structural units is 1-3% by weight.
8. The tandem solar cell according to claim 1, characterized in that: The tunneling layer further comprises a conductive agent; the conductive agent comprises one or more of graphene, conductive carbon black and carbon nanotubes; And / or, the particle size of the conductive agent is 5 to 5000 nm; And / or, based on the total weight of the tunneling layer, the content of the conductive agent is 20-50 wt %.
9. The tandem solar cell according to claim 1, characterized in that: The carrier mobility of the tunnel layer is 10 2 ~10 4 cm 2 / VS.
10. The tandem solar cell according to claim 1, characterized in that: The thickness of the tunneling layer is 1-300 nm.
11. The tandem solar cell according to claim 10, characterized in that: The thickness of the tunneling layer is 5-50 nm.
12. The tandem solar cell according to claim 1, characterized in that: The perovskite top cell comprises a stacked hole transport layer, a perovskite absorption layer, an electron transport layer and a conductive electrode; the hole transport layer is laminated with the tunneling layer; The bottom cell is a crystalline silicon bottom cell.
13. The tandem solar cell according to claim 12, characterized in that: The thickness of the hole transport layer is 20-500 nm; the total thickness of the hole transport layer and the tunneling layer is 50-800 nm; The thickness of the perovskite absorption layer is 300-800 nm; the band gap of the perovskite absorption layer is 1.6-1.8 eV; The thickness of the electron transport layer is 20-100 nm.
14. The tandem solar cell according to claim 12, characterized in that: The perovskite absorption layer comprises one or more compounds having the general formula shown in the following formula (1): ABX3 formula (1); where A is selected from Cs + 、C2H8N + 、CH5N2 + and CH6N + One or more of the following; B is Pb 2+ ; X is selected from Cl - Br - and I - One or more of; and / or The crystalline silicon bottom cell is selected from one of PERC, TOPCon and HJT.
15. A photovoltaic module, characterized in that: A stacked solar cell comprising the layered solar cell described in any one of claims 1 to 14.